1992
DOI: 10.1111/j.1467-842x.1992.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Change‐over Designs for Autocorrelated Observations

Abstract: Some aspects of design of changeover experiments with autocorrelated observations are investigated. Wfiams' designs (1949, 1950) are seen to be balanced for autocorrelated observations. Acknowledgements. T h e author thanka the referee and an assodate editor for helpful comments and suggestions. -(1950). Experimental desigm balanced for pairs of residual dects. Austral. J. SU. Res. Ser. process. Austral. J. Statist. 26, 179-188. autoreppssive process. The Statist. 34, 161-173. A 3, 351-363.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Because their information matrix C τ in (19.11) is completely symmetric it follows, of course, that comparisons between two direct effects are estimated with the same variance. Gill (1992) investigated this property for the case of autocorrelated errors (remember that C τ is now a function of ρ). He found that for p ≤ t and t a prime or prime power the method proposed by Williams (1949) can be used to construct a balanced design with t (t − 1) subjects.…”
Section: Autocorrelation Error Structurementioning
confidence: 99%
“…Because their information matrix C τ in (19.11) is completely symmetric it follows, of course, that comparisons between two direct effects are estimated with the same variance. Gill (1992) investigated this property for the case of autocorrelated errors (remember that C τ is now a function of ρ). He found that for p ≤ t and t a prime or prime power the method proposed by Williams (1949) can be used to construct a balanced design with t (t − 1) subjects.…”
Section: Autocorrelation Error Structurementioning
confidence: 99%
“…Correlated observations models for CODs in the presence of carryover effects were discussed by Finney (1956), Taka and Armitage (1983), Laska and Meisner (1985), and Gill and Shukla (1987). Gill (1992) found that generalized least squares estimation of direct treatment effect and first-order carryover effect for CODs under autocorrelated observation model is very difficult. An easy way out is to consider a design that is robust to correlation structure similar to Ipinyomi (1986), who introduced a class of block designs called equineighbored block designs in which each treatment is paired with other treatments in every plot position.…”
Section: Introductionmentioning
confidence: 98%
“…An inaccurate analyzed of a study can produce misleading results for that study. Repeated measures experimental designs require special attention, since in practice the observations within each subject are more likely to be correlated with different covariance structures that makes their analysis different from other factorial experiments (Bellavance et al, 1996;Gill, 1992;McCulloch, 2003). Considering the right covariance structure for the observations within each subject is an important aspect of the analysis of repeated measures experiment; this is where the dependency due to the repeated measures is taken into account.…”
Section: Introductionmentioning
confidence: 99%